Quetzal Route. The adventure in person (Journal of Parents and Teachers, 1996)
The article describes the experience of 450 young people from 30 countries who participated in the 1995 Ruta Quetzal, a 50-day adventure in Ecuador and Peru. The program, supported by the Spanish Ministry of Foreign Affairs and UNESCO, seeks to promote cultural exchange and personal growth. Participants were selected based on competitions and academic merit.
Keywords: cultural exchange; personal growth; youth